Requirements engineering for crossover services: Issues, challenges and research directions - Zhengli Liu; Bing Li; Jian Wang; Rong Yang (IET Software)
Abstract Crossover services involve deep convergence of services in different domains. Requirements analysis of crossover services often requires the collaboration of engineers in different domains and various organizations. The industry has a demand for sophisticated requirements engineering (RE) methods to address challenges brought by crossover and convergence. However, many methods proposed by researchers have not been widely used in the industry, and the reason is that these methods provide technological solutions to the problems and challenges that may not be considered accurate or even real by practitioners in the crossover services industry. A great effort is needed to explore what needs, expectations, and constraints that RE approaches must satisfy and promote the adoption of novel RE approaches in the crossover services industry. The authors have conducted an industrial study to gain an in‐depth understanding of practitioners' needs concerning RE research and method development. The study involved qualitative interviews as well as questionnaires to collect data. The objective of this study is to investigate issues, challenges, and practices of crossover services RE from practitioners' perspectives and to reveal potential guidelines for researchers and tools developers. Findings from five aspects of RE methods are reported and some research directions for future crossover services RE research are provided.